Butterflies (Lepidoptera: Hesperioidea and Papilionoidea) of the Moldo-Too Range (Inner Tien-Shan): faunistic analysis and vertical distribution - Stanislav K. Korb (Трансформация экосистем, 2021)
Data on the fauna and vertical distribution of butterflies of the Moldo-Too Mountain Range (Inner Tien Shan) are presented. The material for research was collected during 12 summer seasons at 9 points of the ridge. The fauna of this mountainous region includes 118 species of Rhopalocera: 9 species of Hesperiidae, 7 species of Papilionidae, 15 species of Pieridae, 21 species of Nymphalidae, 23 species of Satyridae, 1 species of Riodinidae and 42 species of Lycaenidae. The vertical distribution of this fauna on the Moldo-Too Range is as follows: 79 species in low mountains,100 species in middle mountains, 60 species in high mountains and 31 species in ultrahigh mountains. The distribution of this fauna on the key habitats is as follows: 91 species in steppes, 105 species in dry meadows, 57 species in wet meadows, 14 species in screes, 23 species in rocks and rocky places and 18 species in the bushes. It is shown that the faunas of the low and middle mountains, high and ultrahigh mountains are similar, and that the faunas of two of the six key biotopes (steppes and dry meadows) are similar; possible causes of this similarity are discussed.